From self-disorders to ego disorders - Fuchs, Thomas (Psychopathology, 2015)
While the concept of disorders of basic self-experience as the clinical core of schizophrenia spectrum disorders has gained increasing significance and empirical support, several questions remain still unresolved. One major problem is to understand how the basic and prodromal self-disturbances are related to Schneider's first rank symptoms, in particular to the so-called ‘ego disorders' found in acute psychotic episodes. The study of the transition from prodromal to first rank symptoms, for example from alienated thoughts to thoughts aloud or thought insertions, is of particular importance for understanding the nature and course of schizophrenia. The paper analyses the emergence of ego disorders from basic self-disorders in phenomenological terms, taking the examples of motor passivity experiences and thought insertion. It is argued that full-blown delusions of alien control are ultimately based on a disturbance of the intentionality of thinking, feeling and acting. This disturbance, for its part, may be traced back to anomalies of self-experience in prodromal stages of schizophrenia.
Gesehen am 16.06.2020